Vloga zdravnika družinske medicine pri zdravljenju in rehabilitaciji bolnika z rakom - Tušek-Bunc, Ksenija (Rehabilitacija (Ljubljana), 2008)
Cancer diseases present an important public health issue in the world as well in our country. The prevalence of malignancies is continuously rising in the past years. The advances in medical technology contribute to better outcomes, which add additional problems, how to return to their social and working environment. Family physician has to poses knowledge on diagnostic, treatment and rehabilitative options in order to plan all those activities from the beginning of the cancer care. Family practice management of cancer patients must be holistic and comprehensive, as cancer patients usually have besides cancer also several other conditions. The main role of family physicians in cancer care is prevention and long term care. The main tools to diminish morbidity and mortality due to cancer diseases are early identification of risk factors and recommendations for a healthier life style. In cancer patients pain relief is a very important task of family physicians, which only one step in the rehabilitation process followed by life style modification and other aspects of rehabilitative activities, i.e. psychosocial support, adaptation of working and living conditions. Support to the families plays an important part of family practice. The main emphasis is in timely and quality rehabilitation activities, the ultimate aim but patient's quality of life. Family physician has to collaborate with other members of the team.
Keywords: družinska medicina; onkologija; rak (medicina); rehabilitacija; zdravljenje